MENINGKATKAN KEMAMPUAN BAHASA PADA ANAK PRASEKOLAH (4-6 TAHUN) DENGAN METODE PERMAINAN - Ru'iya, Sutipyo (AL-MISBAH (Jurnal Islamic Studies), 2013)
A human being is born in a state of fitrah (bring potential) are ready to be developed. Every human capabilities that should be in the teaser (stimulus) in such a way as to develop the maximum. Similarly, the ability of language to a child should be given as early as possible so that stimuli can be maximum development. To achieve maximum progress on aspects of child language development, this article offers a method that is the game. According to many research results, giving the game assessed affective stimuli in children's language development.